1990
DOI: 10.1111/j.1365-2591.1990.tb00798.x
|View full text |Cite
|
Sign up to set email alerts
|

Predominant obligate anaerobes invading the deep layers of root canal dentine

Abstract: This study was carried out to investigate the presence and types of bacteria invading the deep layers (0.5-2.0 mm from the surface of the root canal wall) of infected dentine of human root canals by sampling with an anaerobic glove box system the split surfaces of eight freshly extracted teeth. More bacteria were recovered after incubation in an anaerobic glove box than after aerobic incubation in air with 30 per cent CO2. Out of 256 predominant bacterial isolated, 205 isolates (80 per cent) were obligate anae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
125
0
15

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(146 citation statements)
references
References 13 publications
6
125
0
15
Order By: Relevance
“…The canals that sampled bacteria in the present study following Ca(OH)2 had high initial counts at S1. Ando and Hashino (34) showed that bacteria invade deep into the dentin. They found that bacteria extended into dentin 2 mm from the dentin/canal border.…”
Section: Discussionmentioning
confidence: 99%
“…The canals that sampled bacteria in the present study following Ca(OH)2 had high initial counts at S1. Ando and Hashino (34) showed that bacteria invade deep into the dentin. They found that bacteria extended into dentin 2 mm from the dentin/canal border.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the dentin wall of an infected root canal can harbor bacteria or bacterial metabolic by-products (1,2). An intense bacterial penetration to about 300 µm deep into the dentinal tubules has been reported (2,3); penetration depths >500 µm (4) and high prevalence in cases of persistent apical periodontitis (5) have been reported for Enterococcus faecalis.…”
Section: Introductionmentioning
confidence: 99%
“…Daha kontrollü, etkili ve hızlı bir iyileşme elde edileceğine inanılmaktadır. LSDT tedavisinde hedef bakterilerin belirlenebilmesi için çürüklü dentin, [15][16][17] pulpa, 18 enfekte kök dentini ve nekrotik pulpa, 11,19 periradiküler lezyonlar ve enfekte sement 20 37 ise, yapmış oldukları bir in vitro çalışmada enfekte dentin, enfekte pulpa ve periapikal lezyonların oluşumunda etkin bakterilere karşı üçlü antibiyotik karışımının antibakteriyel etkinliğini tek tek ve karışım olarak karşılaştırmışlardır. Tek başına hiçbir antibiyotiğin bakterileri tamamen ortadan kaldıramadığını, ancak karışım halinde tüm örneklerin steril olduğunu tespit etmişlerdir.…”
Section: Tedavi Yönteminin Gelişimiunclassified